Loss of function of the stomatognathic apparatus in relation to chewing capacity and aesthetic factor in children aged 7 to 10 years - Olaguivel Flores, Vilma Fortunata (2024)
The purpose of this research was to determine the loss of function of the stomatognathic system in relation to the chewing capacity and aesthetic factor in students from 7 to 10 years old at the Independencia School - Puno 2022. Method, it is basic in scope, explanatory, quantitative, non-specific design. experimental, transversal. 186 children aged 7 to 10 years participated, whose oral cavity was examined in order to determine the number of lost teeth. Descriptive statistics and inference were used to corroborate the hypothesis. The results from the statistical results and analysis of data obtained determine the loss of function of the stomatognathic apparatus in 16.54%, in relation to the chewing capacity and the aesthetic factor. In conclusion: The loss of function of the stomatognathic apparatus has an impact on the chewing capacity and the aesthetic factor in the group of boys and girls from 7 to 10 years old at Colegio Independencia - Puno 2022.